A naphthalimide-based turn-on fluorescence probe for peroxynitrite detection and imaging in living cells. Issue 63 (16th October 2020) - Liu, Xiling; Gu, Fangyuan; Zhou, Xinyi; Zhou, Wei; Zhang, Shuping; Cui, Lei; Guo, Ting
Abstract : A novel fluorescent probe HCA-OH was designed for selective detection of peroxynitrite and imaging in HepG2 cells and C. elegans. Abstract : Peroxynitrite (ONOO − ) is a potent biological oxidant that plays a significant role in diverse physiological and pathological processes. A novel fluorescent probe HCA-OH was developed for specific and sensitive detection of peroxynitrite, and displayed a significant fluorescence turn-on signal. With low cytotoxicity and good photostability, the probe HCA-OH could be applied in imaging ONOO − distribution in HepG2 cells and live C. elegans in real time. Therefore, the probe can be a promising tool for imaging in vivo .